2017
DOI: 10.1371/journal.pone.0172466
|View full text |Cite
|
Sign up to set email alerts
|

SlMAPK3 enhances tolerance to tomato yellow leaf curl virus (TYLCV) by regulating salicylic acid and jasmonic acid signaling in tomato (Solanum lycopersicum)

Abstract: Several recent studies have reported on the role of mitogen-activated protein kinase (MAPK3) in plant immune responses. However, little is known about how MAPK3 functions in tomato (Solanum lycopersicum L.) infected with tomato yellow leaf curl virus (TYLCV). There is also uncertainty about the connection between plant MAPK3 and the salicylic acid (SA) and jasmonic acid (JA) defense-signaling pathways. The results of this study indicated that SlMAPK3 participates in the antiviral response against TYLCV. Tomato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 101 publications
(128 reference statements)
5
46
0
Order By: Relevance
“…PR1a is SA‐responsive and considered a systemic acquired resistance (SAR) marker (López‐Ráez et al ., 2010; Martínez‐Medina et al ., 2013). PR1b is up‐regulated by both SAR and ISR activation (Harel et al ., 2014; Li et al ., 2017). Distinctions between ISR and SAR are not clear‐cut in tomato, and they can overlap (Liu et al ., 2016; Betsuyaku et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…PR1a is SA‐responsive and considered a systemic acquired resistance (SAR) marker (López‐Ráez et al ., 2010; Martínez‐Medina et al ., 2013). PR1b is up‐regulated by both SAR and ISR activation (Harel et al ., 2014; Li et al ., 2017). Distinctions between ISR and SAR are not clear‐cut in tomato, and they can overlap (Liu et al ., 2016; Betsuyaku et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Other kinases implicated in defense signal transduction pathways have also been manipulated to mitigate viral symptoms. Overexpression of SlMAPK3, a MAP kinase, showed enhanced expression of defense genes associated with SA- and JA-signaling, lower accumulation of reactive oxygen species, increased accumulation of antioxidant enzymes, and stronger tolerance to tomato yellow leaf curl virus infection as expressed by a 2-week delay in symptom induction which was sufficient to allow plant flowering ( Li et al, 2017 ). Similarly, overexpression of OsCIPK30, a kinase involved in calcium signaling, in rice provided enhance tolerance to rice stripe virus, that was associated with delayed and milder symptoms and enhanced expression of PR genes ( Liu et al, 2017 ).…”
Section: Engineering Tolerance To Virus Disease For Field Applicationmentioning
confidence: 99%
“…Activation of SA also plays a role in tolerance of A. thaliana to P. syringae [ 115 ]. Analyses by Li et al [ 116 ] also suggested that SA and jasmonic acid could be involved in tolerance of tomato to TYLCV.…”
Section: Mechanistic Basis and Genetic Determinants Of Plant Tolermentioning
confidence: 99%